Japan – U.S. Relations under the Abe Doctrine: Shifting Policy in East Asia Regional Stability - Manurung, Hendra (Penerbit Universiti Utara Malaysia, 2017)
Reelection of Shinzo Abe as Prime Minister provides a favorable climate for both Donald Trump’s first presidential visit to Japan and an improvement of Chinese-Japanese-U.S. bilateral relations. In the 22 October 2017 ballot, Abe’s dominant Liberal Democratic Party (LDP) and its coalition partner Komeito, secured a two-thirds majority in the House of Representatives, the lower house of Japan’s bicameral legislature. The coalition already holds a supermajority, required for amending the constitution, in the upper house. It justified Abe for calling the national elections a year earlier than needed to secure a public mandate for addressing the growing North Korean threat and to validate popular support for deepening national economic reforms, which have had recent success in boosting Japan’s growth rate and the stock market.Still the outcome gave Abe a mandate for his policies.However, his stewardship was unclear as several other factors contributed to LDP’s overwhelming victory.At the structural level, Japan’s first past the post-electoral system tends to amplify electoral wins in comparison to proportional representation systems. Abe’s foreign and security policies highly charged with ideological revisionism contain the potential to shift Japan onto a new international trajectory in East Asia. Its degree of articulation and energy makes for a doctrine capable of displacing the Yoshida Doctrine that has been Japan’s dominant grand strategy in the post-war period. Abe will remain pragmatic and not challenge the status quo.However, Abe has already begun to introduce radical policies that appear to transform national security, US-Japan alliance ties and relations with China and East Asia. The Abe Doctrine is dynamic but high risk.Abe’s revisionism contains fundamental contradictions that may ultimately limit national effectiveness.